SISTEM EKONOMI SYARIAH DALAM BINGKAI FIQH MUAMALAH MENGHADAPI TANTANGAN MASYARAKAT EKONOMI ASEAN - Nofiardi, Nofiardi (Alhurriyah, 2016)
According to some economists, especially Muslim economists, the current world community has experienced saturation with the capitalism and socialism economic system . In addition, by developing both the economic system, the world is increasingly irregular, which in turn gave birth to the countries that are increasingly rich on one side and the countries getting poorer on the other side. By looking at these facts, the new idea that offers the Islamic doctrine of the economy as an economic system appears. Even Jacquen Austry, a French economist says that the way to grow the economy is not limited to the two mazhab that have been recognized; capitalism and socialism, rather than that, there is a third stronger economy mazhab, (so called) Islamic economics. He argues that the Islamic economic system will rule the world someday because this is a perfect composition of life. On the other hand, the most important issue (emergency) in public life is "muamalah" governing the relationship between the individual and the community in economic activity. Even the scholars agree on the absoluteness of Muslims in understanding and know the sharia economic laws.